Changes of Dry Eye Related Markers and Tear Inflammatory Cytokines After Upper Blepharoplasty - Zhao, Songjiao; Song, Nan; Gong, Lan (Frontiers in Medicine, 2021)
Objectives: To investigate the changes of dry eye-related clinical manifestations, ocular surface parameters, and tear inflammatory cytokines after upper blepharoplasty. Methods: Forty eyes of 20 who underwent upper blepharoplasty were divided into either the group with or the group without preexisting dry eye before upper blepharoplasty. Ocular Surface Disease Index (OSDI), Schirmer I test, tear meniscus height, lipid layer thickness, noninvasive tear break-up time (NIKBUT), fluorescein tear film break-up time (FBUT), corneal fluorescein staining, meibum expression, lid margin changes, and tear inflammatory cytokines were assessed preoperatively and at 1, 3, and 6 months postoperatively. Correlations between inflammatory cytokines and dry eye-related parameters were determined. Results: The OSDI scores increased significantly at 1 month (p = 0.040) and subsequently decreased to the preoperative levels at 6 months postoperatively in subjects with dry eye. First (f)-NIKBUT and FBUT were significantly shortened at 1, 3, and 6 months postoperatively in subjects with dry eye (f-NIKBUT: p＜ 0.001, p = 0.010, p = 0.042; FBUT: p = 0.002, p = 0.005, p = 0.037, respectively), but were only shortened at 1 month (p = 0.028, p = 0.005) and returned to baseline levels at 6 months postoperatively in subjects without preexisting dry eye. A significant increasing trend of interleukin (IL)-6 was found in both dry eye and subjects without preexisting dry eye (p = 0.016, p = 0.008), while IL-8 and tumor necrosis factor alpha (TNF-α) were only found to be increased in subjects with dry eye postoperatively (p = 0.031, p = 0.031). The levels of IL-8 and TNF-α were positively correlated with OSDI scores (p = 0.046, p = 0.043, respectively) and negatively correlated with f-NIKBUT and FBUT (p = 0.026, p = 0.006, respectively). Conclusions: Upper blepharoplasty might increase the release of tear inflammatory cytokines and tear film instability that contribute to the development of postoperative dry eye in the early postoperative period and the changes most relieved in 6 months. Preexisting dry eye is a higher risk factor for worse and persistent ocular surface damage after upper blepharoplasty.